Microbial Analysis of Barleria prionitis Linn: Microbial Analysis of Barleria prionitis Linn - Dheer, Dr. Reema (International Journal of Pharmaceutical & Biological Archive, 2018)
Meicinal plant materials carry a great number of bacteria and moulds from soil. The current practices of harvesting, handling and production of herbs often cause additional microbial contamination. The pathogenic bacteria normally seen in the plant materials are Escherichia coli, Salmonella sp., Pseudomonas aeruginosa, and Staphylococcus aureus (Indian Herbal Pharmacopoeia). The Indian Herbal Pharmacopoeia also specifies limit for E. coli, and Salmonella sp. for medicinal plant material (Trease and Evans, 1985). Before coming to the market, the herbal drug should be made free from any pathogens, bacteria, moulds or fungi. If heating is not involved in manufacturing process, herbs should be properly sterilized by ethylene oxide or gamma radiation. The WHO has also emphasized for the control of microbial contamination in plant materials and prescribed guidelines for testing total viable count, E. coli, and Salmonella sp. in the plant materials (Kokate, 1991). In the present study culture media were prepared as per the formula and procedure given in Indian Pharmacopoeia 1996 Vol-II. Total aerobic microbial count of the sample of leaf and root of Barleria prionitis were determined. Total Viable Count, Fungal Count and tests for specific microorganisms in sample of leaf and root of B. prionitis was determined. In the sample of leaf, E. coli, Salmonella, and Staphylococcus were found negative, but Pseudomonas was found positive. In the sample of root, E. coli and, Staphylococcus were negative, but Salmonella and Pseudomonas were found positive. The absence of Staphylococci could be ascribed to the absence of human and animal’s contamination. The present study and its findings would serve as an important source of information helpful in establishing the purity and efficacy of the plant.